Representation of Chaude Rajlok, a concept in Jain traditions and cosmology - Temples of India Project Team (Jio Institute, 2024)
The painting in the inner/upper circle in the ceiling of the mandapa (pillared hall) represents Chaude Rajlok, a concept in Jain traditions and cosmology that signifies four celestial realms or heavenly abodes. These realms are regarded as higher spiritual dimensions in Jainism, representing stages of spiritual evolution and attainment of purity, leading to liberation from the cycle of birth and death. The painting has a pyramid with a Tirthankara positioned at its apex. The inscription reads, ‘Chaude Rajlok.’